Big data technologies and applications : 7th International Conference, BDTA 2016, Seoul, South Korea, November 17-18, 2016, Proceedings /: 7th International Conference, BDTA 2016, Seoul, South Korea, November 17-18, 2016, Proceedings. (2016) - Unknown
No abstract available